Impacto de los precios del petróleo en época de covid-19 en la economía de Estados Unidos (2021)
This document presents as its main objective, to find the impact that the variation in oil prices has had in the United States at the time of the coronavirus and how this pandemic affected the economy. Based first on an analysis of which factors affect oil prices, then expose the sectors of the economy that were most affected by oil prices in addition to the Covid-19 pandemic.Finally, a strategy is presented that can benefit the U.S. economy as well as stabilize the country's energy balance as is the energy transition. Once these aspects have been determined, mechanisms of action are proposed as well as strategies implemented by other countries that have benefited and presented positive results